SIMULASI INTERKONEKSI PLTS APUNG DI DANAU BATUR DENGAN PENYULANG KINTAMANI - Jaya Kusuma, I Kadek Bagus; Satya Kumara, I Nyoman; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p35, 2023)
Lake Batur has the potential to build a floating solar power plant to improve voltage drop disturbances. The author uses three scenarios using power flow analysis and transient analysis for each scenario in Kintamani. Scenario 1 with a floating solar power plant capacity of 10 MW has a positive impact by increasing the busbar voltage value but there are reverse power conditions that can disrupt the power system at the Payangan Substation. Scenario 2 with a floating PLTS capacity of 1.2 MW has a positive impact by increasing the voltage value and does not cause reverse power at Payangan Substation. Scenario 3 with a floating PLTS capacity of 3 MW has a positive impact by being able to increase the voltage value and does not result in reverse power at Payangan GI. When the floating solar power plant loses power production, it causes a decrease in voltage value, then the system stabilizes again.